W 50 rocznicę śmierci Marszałka Józefa Piłsudskiego [znaczek podziemny] . For the 50 anniversary of the death of Marshal Józef Piłsudski. Unofficial stamp - Wydawnictwo In Corpore. (Wydawnictwo In Corpore, 1985)
Black print on white paper, without perforation. Stamp, with "Wydawnictwo In Corpore" imprint represents Marshal Józef Piłsudski against the background with the emblem of Poland (eagle with a crown). Price: 50 zł per stamp.